2007
DOI: 10.1126/science.1145876
|View full text |Cite
|
Sign up to set email alerts
|

Social Comparison Affects Reward-Related Brain Activity in the Human Ventral Striatum

Abstract: Whether social comparison affects individual well-being is of central importance for understanding behavior in any social environment. Traditional economic theories focus on the role of absolute rewards, whereas behavioral evidence suggests that social comparisons influence well-being and decisions. We investigated the impact of social comparisons on reward-related brain activity using functional magnetic resonance imaging (fMRI). While being scanned in two adjacent MRI scanners, pairs of subjects had to simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
397
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 548 publications
(422 citation statements)
references
References 21 publications
21
397
1
3
Order By: Relevance
“…These findings thus imply that the subjects are less able to implement costly punishment following disruption of the function of the right lateral PFC, due to the lack of prefrontal-mediated modulation of economic self-interests. On the other hand, the right dorsal striatum, a brain area strongly implicated in reward processing [Delgado et al, 2003;Fliessbach et al, 2007;Liu et al, 2007;O'Doherty et al, 2004], has also been demonstrated to be activated during second-party punishment decisions [de Quervain et al, 2004], consistent with the view that this brain area motivates and reinforces the punishment act. Taken together, the increased activity of these two brain regions during both second and third-party norm enforcement processes indicates, as hypothesized, that the implementation of both second and third-party punishment decisions rely on similar neural circuitry.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These findings thus imply that the subjects are less able to implement costly punishment following disruption of the function of the right lateral PFC, due to the lack of prefrontal-mediated modulation of economic self-interests. On the other hand, the right dorsal striatum, a brain area strongly implicated in reward processing [Delgado et al, 2003;Fliessbach et al, 2007;Liu et al, 2007;O'Doherty et al, 2004], has also been demonstrated to be activated during second-party punishment decisions [de Quervain et al, 2004], consistent with the view that this brain area motivates and reinforces the punishment act. Taken together, the increased activity of these two brain regions during both second and third-party norm enforcement processes indicates, as hypothesized, that the implementation of both second and third-party punishment decisions rely on similar neural circuitry.…”
Section: Discussionsupporting
confidence: 56%
“…Evidence from transcranial magnetic stimulation (TMS) [Knoch et al, 2006;van 't Wout et al, 2005] and transcranial direct current stimulation (tDCS) [Knoch et al, 2008] studies suggests that the right lateral PFC is causally involved in (costly) norm enforcement behavior by modulating the weight of self-interest in the decision process. On the other hand, punishment-related activity in the dorsal caudatus (a brain region strongly implicated in the processing of rewards that accrue as a result of goaldirected actions [Fliessbach et al, 2007;Kawagoe et al, 1998;O'Doherty et al, 2004;Schultz and Romo, 1988]) in combination with behavioral and questionnaire measures suggests that people derive satisfaction from punishing norm violators [de Quervain et al, 2004;Singer et al, 2006]. We expect similar processes and associated brain activity patterns in the right lateral PFC and the dorsal caudatus when third-parties strongly punish outgroup members (for defecting against cooperating ingroup members).…”
Section: Introductionmentioning
confidence: 81%
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 84%
“…Building on extensive behavioral studies in the domain of social psychology, the past decade has witnessed an increased interest in unveiling the neural signatures of social comparison [Bault et al, 2011;Beer and Hughes, 2010;Fliessbach et al, 2007;Hughes and Beer, 2013;Luo et al, 2015;Wu et al, 2012]. To have participants compare themselves to others, these studies usually employed experimental paradigms in which participants are exposed to both their own and another person's/group's performance or outcomes [Boksem et al, 2011;Fliessbach et al, 2007;Qiu et al, 2010;Zhen et al, 2016;Zink et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation